Globalisasi dan Pembangunan Infrastruktur Maritim Indonesia di Bidang Konektivitas dan Sistem Logistik (2014—2019) - Fachri Pramuja; Fredy Buhama Lumban Tobing (Intermestic: Journal of International Studies, 2020)
Economic globalization is a critical point for the study of international political economy. This paper examines the big picture of economic globalization of the country's domestic policies which is in this case the development of maritime infrastructure in the era of President Joko Widodo (2014-2019). Using the concept of state capacity as a tool of analysis, this paper explores the new reasons for prioritizing the development of Indonesia's marine infrastructure which was massively carried out under Joko Widodo's administration. In this paper, economic globalization is seen through the ability of the state to provide basic facilities in maritime infrastructure development with the aim of building efficiency and innovation in creating a level of sustainable competitiveness for Indonesia's economic growth. The findings in this study explain that [1] the realization of maritime infrastructure development in Indonesia is still more in the planning phase so that it does not significantly reduce logistics costs between the western and eastern regions of Indonesia, [2] there are discrepancy in government rhetoric on achieving maritime infrastructure development with its implementation. Keywords: Economic Globalization, Maritime Infrastructure, Indonesia’s Development.